IMPLIKASI PERKEMBANGAN PERUMAHAN TERHADAP PENGGUNAAN LAHAN DI DESA BONGAN, KABUPATEN TABANAN, BALI. - Benny Williyanto; I Made Gde Sudharsana (UNHI PRESS, 2020)
The resulting growth and population density also affects the use of existing space. This is evidenced by the process of land conversion that is so rapid due to urban activity is extended to the edge of the city. Bongan Village is a part of Tabanan District which is located on the strategic urban outskirts, so it has a good appeal to be a residential area or commercial area. With its strategic location it will certainly affect the agricultural land in Bongan Village whose land use conditions are shifting. Therefore, The purpose of this study is to identify the development of agriculture land conversion into non-agricultural land and analyze the socio-economic conditions of the community related to the conversion of agricultural land there. This study uses spatial analysis to calculate the area of land change and describe the socio-economic condition. Based on the results of the identification and tracking of secondary data of agricultural land area recently decreased every year even almost more than 1 Ha of agriculture land converted into residential land, public infrastructure and road infrastructure development. In 2013 the planting area of Bongan Village is 464 Ha while in 2014, 2015 planting area in Bongan Village of 232 Ha so it can be seen the decrease of agricultural land area in Bongan Village.